Sorbates and benzoates in meat and meat products: Importance, application and determination. Issue 1 (October 2021) - Bajcic, A; Petronijevic, R B; Sefer, M; Trbovic, D; Djordjevic, V; Ciric, J; Nikolic, A
Abstract: Recent views on the use of preservatives sorbic and benzoic acids and their salts in meat products are presented from the point of accordance with current legislation in the Republic of Serbia and the EU, food safety and public health risks, and mainstreams in the methodology for their determination. These preservatives are permitted to be added individually or in combination, the maximum level is applicable to the sum and the levels are expressed as the free acid. Currently set values of the recommended daily intake of sorbate and benzoate are 25 mg/kg and 5 mg/kg, respectively. These values vary and depend on regulations in different countries. Considering control of the use of these additives, the most common methods for their determination are chromatographic methods based on high performance, or high pressure, liquid chromatography with diode array detectors.